A phase-space approach for predicting signal strength in wireless communication systems - Blakaj, Valon (2020)
It has been suggested that the new generation of wireless communication, known as fifth generation (5G), will operate at very high frequencies, ranging from microwave (6 GHz) to mmWave (above 60 GHz). Although, these frequency bands offer the possibility to increase the communication capacity, less is known about the propagation characteristics in indoor and outdoor environments. Wave propagation prediction is a challenging task at these frequencies, and will need new modelling tools in addition to those used to designing current wireless systems, and as well needing to include complexity of the environment at much finer scale.